Estimating Price- Cost Margins and Scale Economies from a Panel of Microdata - Tor Jakob Klette (Statistics Norway, Research Department, 1994)
Hall's (1988) approach to study price- cost margins is adapted to simultaneously estimate price- cost margins and scale economies from a panel of plant level data. The paper shows how this methodology provides a very flexible framework with only a few, economically interesting parameters to be estimated. The econometric model is tested and estimated on different panels of plants, covering most manufacturing industries in Norway 1980- 90. The GMM- estimates suggest significant, but quite small, markups in all industries. No industry exhibits increasing returns to scale; the average firm (in all industries) seems to face constant or moderately decreasing returns to scale. Estimates suggest that there is more variation in the price- cost margins and scale coefficients within the fairly narrow industry groups investigated, as compared to between the industry groups.
Additional information: This paper is a substantially revised version of Klette (1993): "Is Price Equal to Marginal Costs? An Integrated Study of Price Cost Margins and Scale Economies among Norwegian Manufacturing Establishments 1975-90", Discussion Paper No. 93, Statistics Norway.
Keywords: D40; C23; 330; Market power; scale economies; GMM; specification testing; establishment data